ANALISIS BAURAN PROMOSI UNTUK MENINGKATKAN VOLUME PENJUALAN Unit Susu Sapi Perah Koperasi Unit Desa (KUD), Jl. Kolonel Matsuri Desa Jambudipa Kec. Cisarua, Bandung 40551 - Dewi, Erminawati; Firdaus, Evan; Arisena, Adri; Sumaryana, Fitriana Dewi (IKOPIN, 2021)
The research was motivated by the problem of declining sales of KUD Sarwa Mukti in the Cow Milk Unit. The Dairy Cattle Business currently accommodates 236,580 liters of milk produced by members per month in 2019, in 2018 it accommodates members' milk production of 413,535 liters per month. In 2019 the production of dairy cows decreased by 176,955 liters, this was due to the termination of cooperation with a company PT. Cimory due to the impact of Covid- 19. To be able to increase the sales volume of cow's milk, a sales promotion is needed, with a good sales promotion it can increase sales volume and the cooperative's dairy cow is more widely known by the public.This research is: (1) Knowing the promotional mix applied in KUD Sarwa Mukti to increase sales volume, (2) Knowing what factors can increase the promotion mix in the dairy unit of KUD Sarwa Mukti, (3) Knowing the efforts What are the efforts made by KUD Sarwa Mukti to increase sales volume in the dairy unit of dairy cows.The results showed that the promotional mix carried out by KUD Sarwa Mukti was not maximized and the cooperative was still using Word OF Mount Marketing promotions, in 2013 they had time to distribute brochures but only once to introduce more widely to the public. The suggestion put forward by the researcher is that it is recommended to KUD Sarwa Mukti to improve the promotion mix so that the cooperative is better known by the general public outside or inside the city and makes it easier to find information about cow's milk and the condition of KUD Sarwa Mukti and can also compete with other companies in promoting their products for increase sales volume. And always maintain quality and good service to consumers.